PERAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR SISWA KELAS XI IPS DI SMA NEGERI 3 KOTA JAMBI - Aprilia, Sella; Pamungkas, Satriyo (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
This study aims to explain the role of the family environment on the learning outcomes of class XI IPS students in class history at SMA Negeri 3 Jambi City. This type of research is quantitative descriptive, the primary data source is student questionnaires, while the secondary data source is documentation. Based on the results of the research that has been carried out which has been poured into the discussion in each of the previous chapters, it can be concluded that the role of the family in the learning of class XI IPS $ SMA Negeri Jambi City can be known based on the results of the questionnaire, namely. In the indicator of the role of parents on students' learning motivation, the percentage of 61.71% is included in the "Enough" category. Furthermore, the indicator of parental attention to student learning gets a percentage of 67.43% belonging to the "Enough" category. In the next indicator regarding parental discipline towards student learning, the percentage of 70.37% is also included in the "Enough" category. And lastly, the indicator of parents' character on student learning gets a percentage of 68.76% which is included in the "Enough" category. So from all of these indicators, an average of 67.06% is included in the "Enough" category.